Lembaga Negara Dalam Al-Qur’an (Kajian Tafsir Maudhu’i) - Kurniawan, Wawan; Suminar, Sely; Thiebaty, Sofia Zahra; Solahudin, Nabil Ahmad; Muhyi, Asep Abdul (LP2M Universitas Islam Ahmad Dahlan, 2023)
This paper aims to discuss the concept of state institutions in the Qur’an, especially by using Maudhu’i’s Interpretation studies. This writing uses a qualitative method with a library research approach and places more emphasis on the interpretation of the verse, Asbabun Nuzul, and the Mufradat study. Islam regulates all aspects of life, including the leadership and governance of a region. A state institution is a management system established by the government to regulate and manage a country. In the Al-Qur’an there are several verses relating to the term state, but the concept of a state according to the Qur’an whwn it is associated with the meaning of a state that is identical with territorial boundaries and the presence of residents who inhabit it is in the term al-Balad. The meaning of Balad in its editorial is divided into three of them, namely al-Balad, al-Bilad, and Baldah. All three have different meanings, but in general, all of these words point to a place. In Islam, the power or authority of the government is not absolute. Therefore several principles must be upheld and implemented by the goverment itself.